Media Sosial dan Dekadensi Moral Generasi Muda - A.Nur Aisyah Rusnali (Connected: Jurnal Ilmu Komunikasi, 2020)
The purpose of this research is to find out how the use of social media is against the moral decadence of the nation's young generation. This research was conducted using the library research method, where this method is considered effective and efficient during the COVID-19 pandemic. Social media is an inseparable part of human life today, especially for the younger generation who have grown up together with social media. Social media seems to be a lifestyle for today's young generation. Like two sides of a coin, social media provides many benefits because it can keep us connected with people who are separated from us. But on the other hand, the use of social media also often causes moral decadence such as crime, promiscuity, and other immoral acts.